Rapidly Progressive Lung Cysts and Pleural Effusion: A Case Report - Diana Olsen; Charlene Molloy; P. S. Sriram (Case Reports in Pulmonology)
Angiosarcoma is a rare but highly malignant tumor arising from vascular endothelial cells. Angiosarcoma commonly arises from the heart, liver, breast, and skin including the scalp. Angiosarcoma metastasizing to the lungs can present as either pneumothorax, hemothorax, or pleural effusions. They can rarely present as rapidly enlarging thin-walled pulmonary cysts. A review of the literature is included.